2006
DOI: 10.1111/j.1540-8167.2006.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia‐Mediated Ventricular Electrical Remodeling

Abstract: Bradycardic states are associated with myocardial electrical remodeling predisposing to potentially lethal ventricular tachydysrhythmias. We used a novel model of complete heart block (CHB) in the rabbit to test the hypothesis that ventricular activation rate is the primary determinant of early bradycardic electrical remodeling. Chronic endocardial right ventricular demand (VVI) pacing was applied at either the near-physiologic rate of 280 beats/min or at the bradycardic rate of 140 beats/min, beginning immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…3 QT interval prolongation in patients with heart block can be due to medications or acquired repolarization abnormalities. 4,5 In patients with concurrent torsades de points and heart block, the ECG usually shows exaggerated lengthening of the QT interval. 6 Importantly, the QT interval is dynamic and may only be extended just prior to the initiation of torsades de pointes.…”
Section: Diagnosismentioning
confidence: 99%
“…3 QT interval prolongation in patients with heart block can be due to medications or acquired repolarization abnormalities. 4,5 In patients with concurrent torsades de points and heart block, the ECG usually shows exaggerated lengthening of the QT interval. 6 Importantly, the QT interval is dynamic and may only be extended just prior to the initiation of torsades de pointes.…”
Section: Diagnosismentioning
confidence: 99%
“…Studies have shown that chronic bradycardia due to sinoatrial node disease can predispose patients to developing atrial and ventricular tachyarrhythmias. 87 Bradycardia causes ventricular electrical remodeling, manifest on the electrocardiogram by QT interval prolongation. This is due to repolarization abnormalities resulting from reduced expression of the rapidly (I Kr ) and slowly (I Ks ) activating delayed-rectifier currents.…”
Section: Govindan Et Al 45smentioning
confidence: 99%
“…3 , 4 However, there are few reports of myocardial remodeling and cardiomyopathy due to bradycardia with blocked atrial bigeminy. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Similar to abnormal persistent tachyarrhythmia, severe bradycardia can also induce cardiomyopathy and heart failure 3,4 . However, there are few reports of myocardial remodeling and cardiomyopathy due to bradycardia with blocked atrial bigeminy 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation